تأثير المعاملة بمحلول كلوريد الكالسيوم CaCl2 في جودة ثمار الليمون الحامض من صنف انتردوناتو أثناء التخزين المبرد . - سلمان, فؤاد; علي, علي; محفوض, علاء (Latakia University Journal -Biological Sciences Series, 2018)
The objectives of this study are to investigate the effect of application three concentrations of Calcium Chloride CaCl2 on quality of Citrus Lemon sort Interdonato ( Citrus lemon Var . Interdonato ) at medium maturity stage (the fruit in complete volume with green yellow color) during cold storage, the fruit were brought to cold store immediately after picking, and divided to four groups : first group of fruits dipped in normal water for 120 seconds and then dried and stored directly without any treatment, while the second , third and fourth groups treated with three concentrations of calcium chloride sequently: 1.5% and 2.5% and 3.5% for 120 seconds and then dried and stored directly. the fruit was stored at a temperature of 7 c° and relative humidity 85-90% for a period of 5 months , samples were taken periodically from all transactions and were made a group of chemical analyses on them to study the impact of those treatments on fruits with calcium chloride compared with the control fruit and select the concentration which achieved better results. The results of the experiment showed that the treatment of fruits with calcium chloride had a positive effect on fruit quality comparing with control fruits, It was found that the treatment of fruits with calcium chloride and especially concentrations of 3.5% followed by 2.5% led to reduce the loss of vitamin C and increase the content of the juice, total sugars and total soluble solids. and the natural loss and absolute loss had declined compared with control fruits. هدف البحث إلى دراسة تأثير المعاملة بثلاثة تراكيز من محلول كلوريد الكالسيوم Calcium Chloride (CaCl2) في جودة ثمار الليمون الحامض من صنف انتردوناتو ( Citrus lemon Var . Interdonato ) في مرحلة النضج المتوسط (الثمار كاملة الحجم ذات لون أخضر مصفر ) أثناء التخزين المبرد. إذ أحضرت الثمار إلى أماكن التبريد مباشرة بعد القطاف, وقسمت إلى أربع مجموعات هي: ثمار الشاهد تغمر بالماء العادي لمدة 120 ثانية ثم تجفف وتخزن مباشرة بدون أية معالجة, وثلاث مجموعات من الثمار تعامل بثلاثة تراكيز من محلول كلوريد الكالسيوم هي 1.5 % و 2.5 % و 3.5 % لمدة 120 ثانية ثم تجفف وتخزن مباشرة . وتم تخزين الثمار على درجة حرارة 7 م° ورطوبة نسبية 85 – 90 % لمدة (5) أشهر وتم أخذ عينات بشكل دوري من جميع المعاملات وإجراء مجموعة من التحاليل الكيميائية عليها لدراسة التأثير الذي يحدثه معاملة الثمار بمحلول كلوريد الكالسيوم بالمقارنة مع الشاهد وانتقاء التركيز الذي حقق أفضل النتائج. بينت نتائج التجربة أن معاملة الثمار بمادة كلوريد الكالسيوم كان له تأثير إيجابي في جودة الثمار بالمقارنة مع ثمار الشاهد؛ إذ وجد أن معاملة الثمار بمحلول كلوريد الكالسيوم وخاصة التركيزين 3.5 % يليه 2.5 % أدى إلى تقليل الفاقد من فيتامين C وزيادة المحتوى من العصير والسكريات الكلية والمواد الصلبة الذائبة الكلية, كما انخفضت نسبة الفاقد الطبيعي والمطلق بالمقارنة مع ثمار الشاهد.